HPLC Analysis of Polyphenols in Green Tea Extracts - Shivaprasad, H.N.; Khanam, Salma (Asian Journal of Chemistry, 2010)
HPLC is a popular method of analysis because it is easy to learn and use and is not limited by the volatility or stability of the sample compound. By virtue of its ability to simultaneously separate, identify and analyze the complex mixture of organic substances, HPLC will be highly useful for the analysis of herbal drugs and formulations. Green tea contains polyphenols which constitute one of the most numerous and ubiquitous groups of plant metabolites and are an integral part of both human and animal diets. In the present communication we report the HPLC analysis of the green tea extract.